The impact of the use of smartphones on the individual identity of students of Imam Abdul Rahman bin Faisal University in the Kingdom of Saudi Arabia: An analytical study - Ghazouani, Samia Boubaker (Journal of Humanities & Social Sciences, 2020)
The research aims to know the uses of university students for smartphones and the achieved gratifications and the impact of its uses on the individual identity. The descriptive approach was used to achieve the goal of the research and the questionnaire tool to collect data through distributing it to a sample (200 students) at Imam Abdul Rahman bin Faisal University in the Kingdom of Saudi Arabia. The results of the research showed that 60% of the sample use the smartphone at a rate of three hours and more daily on a regular basis. The university accounts and friends top the list of accounts that you do not follow, and most of the accounts are in Arabic and mainly Saudi. The research revealed that 87% of female students use the real identity in the virtual world and 12.5% ​​use a pseudonym. Recreational sites attract female students first 78%, followed by scientific sites 53%, then news sites 41%, religious sites 24% in addition to shopping sites and literary and cultural sites. In the ranking of social media, WhatsApp ranked first, followed by Twitter, Snapchat, Instagram and finally YouTube. The research also revealed the awareness of female students of the excessive use that sometimes leads to digital addiction and its physical, psychological and intellectual risks. That is why we recommend media campaigns, awareness- raising workshops and seminars to rationalize the use of smartphones in universities and educational institutions in general.